Analysis of Pediatric Facial Fracture Repair Rates and Complications Using California's Office of Statewide Health Planning and Development Database. Issue 6 (28th September 2022) - Chopra, Christina Shree; Neubauer, Daniel C.; Hornacek, Michael; Calvo, Richard; Segal, Rachel; Martin, Matthew; Reid, Christopher M.; Gosman, Amanda A.
Abstract : Background: There exists a paucity of data on which pediatric facial fractures should be surgically repaired and when. In this study, the authors used a California state-wide database to determine the prevalence of facial fractures in the pediatric population and examine, which fractures are repaired. in addition to the timing of the repair, complications and resource utilization of the healthcare system were analyzed. Methods: Pediatric patients under the age of 18 were identified using the California Office of Statewide Health Planning and Development patient discharge database for admissions occurring between January 2015 and December 2018. International Classification of Diseases, Version 10 diagnosis codes were used to classify facial fractures. The associated diagnoses, complications, and number of subsequent repairs patients underwent were analyzed to determine the typical course of pediatric facial fractures. Results: Of the 3058 patients diagnosed with facial fracture, 32% underwent surgical repair (N = 982). The 4 most repaired fractures were mandible (40%), nasal (16.2%), and orbital (15.1%). Surgical intervention steadily increased with age, with a peak in the 12 to 15-year-old cohort. Conclusions: Our analysis found that most fractures were managed nonoperatively, but those that did receive an operation did so during their index admission. In addition, the most repaired fractures were mandibular, nasal, and orbital fractures. The present study represents 1 of the largest pediatric samples to have assessed facial fractures, repair rates, and their sequelae.